Bola-type PEG-linked polyaromatic hydrocarbon-based chemosensors for the "turn-off" excimer fluorescence detection of nitro-analytes/explosives in aqueous solutions. (February 2023) - Sadieva, Leila K.; Kovalev, Igor S.; Taniya, Olga S.; Platonov, Vadim A.; Novikov, Alexander S.; Berseneva, Vera S.; Santra, Sougata; Zyryanov, Grigory V.; Ranu, Brindaban C.; Charushin, Valery N.
Abstract: Diesters of 1-pyrenecarboxylic acid with tri- and tetra - ethylene glycols were prepared and characterized for the first time and their photophysical and sensory properties were investigated. In aqueous solutions these compounds exhibited an intensive excimeric emission at 521 nm, which is attributed to the aggregation-induced fluorescence of the dimers, pre-associated in the ground state. In aqueous solutions an intensive "turn-off" fluorescence response towards common nitro-explosive components, such as 2, 4-dinitrotoluene (2, 4-DNT), 2, 4, 6-trinitrotoluene (TNT), as well as aliphatic nitro compounds, such as pentaerythritol tetranitrate (PETN), 1, 3, 5-trinitro-1, 3, 5-triazinane (RDX) and 2, 3-dimethyl-2, 3-dinitrobutane (DMDNB) was observed via the excimeric emission quenching. For the most representative chemosensor 4a the highest Stern-Volmer fluorescence quenching constant of 8.75 × 10 6  M −1 was observed in the presence of TNT. Graphical abstract: Image 1 Highlights: Bola-type pyrene end-capped fluorescent podands were prepared. Aggregation-induced excimeric emission in aqueous THF was observed. Great "turn-off" response to nitro-aromatic/aliphatic compounds was detected. (0.97–8.75) × 10 −6  M −1 quenching constants & 2–11 ppb LOD were determinated.